2020
DOI: 10.51983/ijiss.2020.10.1.481
|View full text |Cite
|
Sign up to set email alerts
|

Availability and Awareness of Electronic Databases for Teaching and Research by Lecturers in Public Universities in South-West, Nigeria

Abstract: The introduction of databases by university libraries has presented lecturers with opportunities of obtaining accurate, timely and up-to-date information with little effort. However, research reports have revealed that there is low level of awareness of electronic databases by university lecturers. Hence this study investigated availability and awareness of electronic databases for teaching and research by lecturers in public universities in South-west, Nigeria. The objectives of the study were to: ( I ) ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Eiriemiokhale and Ibeun (2017) found that there is a correlation between awareness, accessibility, and usage of library resources. The correlation, according to them, is that what one is not aware of is hardly desired and once something is not desired it will not be needed and once it is not needed, it will not be sought for and once it is not sought for, it will not be available and accessible for use (Idowu and Eiriemiokhale, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Eiriemiokhale and Ibeun (2017) found that there is a correlation between awareness, accessibility, and usage of library resources. The correlation, according to them, is that what one is not aware of is hardly desired and once something is not desired it will not be needed and once it is not needed, it will not be sought for and once it is not sought for, it will not be available and accessible for use (Idowu and Eiriemiokhale, 2020).…”
Section: Methodsmentioning
confidence: 99%